PERSEPSI MAHASISWA ATAS KUALITAS PELAYANAN LABORATORIUM BANK MINI STIE KESATUAN DAN IMPLIKASINYA TERHADAP KEPUASAN MAHASISWA - Muhammad Ariffin; Suharmiati Suharmiati; Andi Yudha Amwilla (JAS-PT (Jurnal Analisis Sistem Pendidikan Tinggi Indonesia), 2018)
The Purpose of this research is to measure the influence of the service quality of Laboratorium Bank Mini on student’s satisfaction. This research was conducted in STIE Kesatuan Bogor with 100 respondents. Data were analyzed using partial least square method. The results showed that the Physical Evidence, Reliability, Responsiveness, Assurance and Empathy has a significant and positive influence on the student satisfaction of Laboratorium Bank Mini STIE Kesatuan. Keywords: Service Quality, Student Satisfaction, Laboratorium Bank Mini.